PEMBERDAYAAN MASYARAKAT PESISIR DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS MELALUI PENGELOLAAN DAN PEMANFAATAN EKOSISTEM MANGROVE SEBAGAI EKOWISATA BERBASIS KEARIFAN LOKAL DAN EKONOMI KREATIF - Nova Yohana; Anuar Rasyid; Yasir Jufri; Nurjanah Nurjanah; Evawani Elysa Lubis; Ahmad Rifqi (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
The activity was carried out in Teluk Pambang Village, Bantan District, Bengkalis Regency. This activity is due to the local community's lack of awareness of the importance of managing and utilizing mangrove ecosystems that have ecological, social, and economic functions. The purpose of this activity is to provide a comprehensive understanding to the community about the importance of mangrove forest management and utilization to maintain environmental balance in coastal areas, the prospect of economically valuable mangrove ecotourism, providing knowledge of the importance of local wisdom values as a support for the attractiveness of mangrove ecotourism development, and the importance of forming a tourism awareness group as a form of active community contribution in utilizing the potential of sustainable community-based ecotourism. This activity's target is the community living in Teluk Pambang Village, especially the Mangrove Management Group and the Local Government. The implementation method starts with the survey and implementation in the field. This activity involved 12 Riau University students from various disciplines. The results obtained from this activity are the active participation of the community to participate in identifying potentials and ideas for developing Mangrove ecotourism and establishing partnerships with the Village Government and mangrove management groups in the context of community empowerment through the management and utilization of mangrove ecosystems as ecotourism based on local wisdom and creative economy in Teluk Pambang Village.